Toward evidence-informed policymaking in Nigeria? A systematic review of agricultural evidence syntheses - Aremu, Toyib (Frontiers in Sustainable Food Systems, 2024)
This article studies the body of agriculture evidence synthesis in Nigeria as a basis for evidenceinformed policymaking (EIPM). EIPM is seen by its advocates as an objective way of identifying problems and proffering solutions that work, given its potential to offer sound bases for choices, helping with more effective decisions, and preventing detrimental policy outcomes. Yet, according to the EIPM literature, policymakers hardly use evidence or use it to justify pre-existing beliefs. At the same time, EIPM is often criticized as being susceptible to bias, especially given the large volumes of research being published that may arrive at different conclusions. One tool that could address these challenges is research evidence syntheses, known to be objective and rigorous, although there is a gap in knowledge on whether they are produced in ways that make them easily usable by decision makers. To bridge this knowledge gap, this study develops an analytical framework from the literature on facilitators and barriers of scientific evidence use to analyse existing agriculture-based evidence syntheses in Nigeria. The analytical framework was used to analyse and identify gaps in these syntheses that may limit their use by decision makers. Based on pre-defined search criteria, we We find 18 19 relevant syntheses that meet our defined criteria, which are more qualitative and useful in defining policy-relevant problems; however, they mostly do not provide quotable economic statistics, solutions to address the problems identified, or implementation strategies. Given the currently limited number of evidence syntheses, especially those evaluating effectiveness of policy solutions, stakeholders interested in strengthening EIPM in Nigeria could facilitate collaborations between policymakers and researchers to popularise policy-relevant evidence synthesis and ensure such are made available and accessible to users in timely and usable formats.